Puyehuemyia chandleri, gen. nov., sp nov (Diptera: Opetiidae): remnant of a Cretaceous biota in Chile - Amorim, Dalton De Souza; Silva, Vera Cristina [UNESP]; Brown, Brian V. (Amer Museum Natural History, 2018)
The first Opetiidae known from the Southern Hemisphere is described-Puyehuemyia chandleri, gen. nov., sp. nov.-based on a female specimen collected in Valdivian forest in the Province of Osorno, south Chile. The Palearctic species Opetia nigra Meigen was also studied, allowing detailed comparisons. Features of the antenna, mouthparts, wing, and terminalia allowed the issue of the position of the family within the Eremoneura to be revisited. The inclusion of Opetiidae in the Platypezoidea is corroborated, possibly in a clade also including Lonchopteridae and Phoridae. The 3-articled condition of the styluslike arista in Puyehuemyia corroborates the hypothesis that the 2-articled condition in Opetia is independently derived, as it is in the Empidoidea and many schizophorans. Puyehuemyia chandleri has female terminalia typical of parasitoid groups, as does Opetia, although their life history is not known. Described Platypezoidea Cretaceous amber fossils are reviewed, and Lonchopterites is considered to be sister to the crown group of Opetiidae. The presence of an Early Cretaceous biogeographical layer in the Valdivian forest, associated with plant and animals disjunct from New Zealand, and similar to the beech forests in the Northern Hemisphere, is discussed.